Exploring the Use of Social Media in English Language Learning - Della Chrystie; Setiani Bintang Eka Saputri (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The rapid development of digital technology has transformed English language learning by providing learners with access to authentic language exposure through social media platforms such as YouTube and TikTok. This study aims to explore the use of social media in English language learning and examine its positive and negative impacts on students’ language skill development. A qualitative descriptive approach was employed through a literature review of national and international studies published between 2024 and 2026. Data were analyzed using thematic analysis. The findings reveal that social media contributes positively to English learning by improving vocabulary acquisition, speaking and listening skills, learner motivation, and opportunities for self-directed learning. Authentic audiovisual content enables learners to engage with language in meaningful and flexible ways. However, several challenges were also identified, including the overuse of informal language, reduced learning concentration due to digital distractions, and decreased face-to-face interaction, which may affect students’ social communication skills. The study concludes that the effectiveness of social media in English language learning depends on the quality of content, the intensity of use, and guidance from teachers and parents. Therefore, appropriate digital literacy practices are essential to maximize the educational benefits of social media while minimizing its potential drawbacks.